Insights Into HIV Knowledge Among Red Cross Youth Members: A Descriptive Study - Mujahidah, Shafira Aulia; Hernawaty, Taty; Kurniawan, Kurniawan (Indonesian Journal of Global Health Research, 2024)
The Red Cross Youth as a school health cadre has various tasks, one of which is to minimize risky behavior in teenagers. Adolescents have the potential to contract HIV if they do not have good knowledge. This potential is increasing, especially in tourist areas such as Pangandaran. The aim of this research was to determine the level of knowledge of RCY members about HIV in Pangandaran Regency. This research uses a quantitative descriptive research method with a cross-sectional approach. The population in this study was all 120 members of RCY SMAN 1 Parigi, Pangandaran Regency. The sampling method used is saturated sampling. The instrument used was HIV-KQ (HIV Knowledge Questionnaire) 18. This research used a questionnaire in the form of Google Formulir. The data analysis technique used is categorical univariate analysis. The research results showed that 40.8% of respondents had high knowledge level, 37.5% had moderate level of knowledge, and 21.7% had low level of knowledge. These results were influenced by the routine provision of material from RCY supervisors and also external parties such as community health centers that held outreaches about HIV.